The Nutraceutical Alliin From Garlic Is a Novel Substrate of the Essential Amino Acid Transporter LAT1 (SLC7A5) - Scanga, Raffaella; Scalise, Mariafrancesca; Rovella, Filomena; Regina, Teresa Maria Rosaria; Galluccio, Michele; Indiveri, Cesare (Frontiers in Pharmacology, 2022)
The plasma membrane transporter LAT1 (SLC7A5) is a crucial player for cell homeostasis because is responsible for providing cells with essential amino acids and hormones. LAT1 forms a functional heterodimer with the cell-surface antigen heavy chain 4F2 (4F2hc; also known as SLC3A2), a type II membrane glycoprotein, that is essential for LAT1 stability and localization to the plasma membrane. The relevance of LAT1 for human metabolism is related also to its altered expression in human diseases, such as cancer and diabetes. These features boosted research towards molecules able to interact with LAT1; in this respect, the recent resolution of the LAT1-CD98 3D structure by Cryo-EM has opened important perspectives in the study of the interaction with different molecules in order to identify new drugs to be used in therapy or new substrates of natural origin to be employed as adjuvants and food supplements. In this work, the interaction of LAT1 with alliin, a garlic derivative, has been investigated by using a combined approach of bioinformatics and in vitro transport assays. Alliin is a nutraceutical that has several beneficial effects on human health, such us antidiabetic, anticarcinogenic, antioxidant and antiinflammatory properties. The computational analysis suggested that alliin interacts with the substrate binding site of LAT1, to which alliin was docked. This data was then confirmed by the competitive type of inhibition measured in proteoliposomes. Interestingly, in the same experimental model, alliin revealed to be also a substrate of LAT1.